2014
DOI: 10.1021/bm5009525
|View full text |Cite
|
Sign up to set email alerts
|

Chain and Pore-Blocking Effects on Matrix Degradation in Protein-Loaded Microgels

Abstract: Factors affecting matrix degradation in protein-loaded microgels were investigated for dextran-based microgels, the sugar-binding protein Concanavalin A (ConA), and the dextran-degrading enzyme Dextranase. For this system, effects of enzyme, protein, and glucose concentrations, as well as pH, were considered. Microgel network degradation was monitored by micromanipulator-assisted light microscopy, whereas enzyme and protein distributions were monitored by confocal microscopy. Results show that Dextranase-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…32 Conversely, microgel degradation has been reported to be influenced by peptide/protein loading. 48 While there is some information regarding the factors affecting loading and release of model peptides to/from microgels, work on microgel-loaded AMPs remains quite sparse thus far. However, Nordstrom et al investigated the incorporation of the antimicrobial peptides LL-37 (LLGDFFRKSKEKIGKEFKRIVQRIKDFLRNLVPRTES) and DPK-060 (GKHKNKGKKNGKHNGWKWWW) in methacrylic acid-based microgels in solution and found that the antimicrobial effects of such systems depended on peptide release, which was promoted for the smaller peptide DPK-060, for low charge density microgels and at a high ionic strength.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Conversely, microgel degradation has been reported to be influenced by peptide/protein loading. 48 While there is some information regarding the factors affecting loading and release of model peptides to/from microgels, work on microgel-loaded AMPs remains quite sparse thus far. However, Nordstrom et al investigated the incorporation of the antimicrobial peptides LL-37 (LLGDFFRKSKEKIGKEFKRIVQRIKDFLRNLVPRTES) and DPK-060 (GKHKNKGKKNGKHNGWKWWW) in methacrylic acid-based microgels in solution and found that the antimicrobial effects of such systems depended on peptide release, which was promoted for the smaller peptide DPK-060, for low charge density microgels and at a high ionic strength.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Some of these factors have also been demonstrated to affect the protection of peptides from proteolytic degradation . Conversely, microgel degradation has been reported to be influenced by peptide/protein loading . While there is some information regarding the factors affecting loading and release of model peptides to/from microgels, work on microgel-loaded AMPs remains quite sparse thus far.…”
Section: Discussionmentioning
confidence: 99%
“…9 The controlled use of microgels as delivery systems for peptide and protein drugs requires a basic understanding of the factors determining peptide/protein loading into, distribution within, and release from, microgels, and how these effects can be controlled by various design elements and external conditions. For microgel dispersions, there have been an increasing number of mechanistic studies dedicated to the effect of microgel properties, e.g., charge 10 and cross-linking density 11 , as well as of peptide properties, such as molecular weight 12 , charge (distribution) 10 , secondary structure 13 , and hydrophobicity 14 , including also effects of biodegradation of both the peptide 15 and microgel network 16 . For surface-bound microgels, on the other hand, there is very limited prior work done in this context.…”
Section: Introductionmentioning
confidence: 99%
“…For microgel dispersions, there have been an increasing number of mechanistic studies dedicated to the effect of microgel properties, for example, charge 10 and cross-linking density, 11 as well as of peptide properties, such as molecular weight, 12 charge (distribution), 10 secondary structure, 13 and hydrophobicity, 14 including also effects of biodegradation of both the peptide 15 and microgel network. 16 For surface-bound microgels, on the other hand, there is very limited prior work done in this context. Hence, it remains to be clarified whether surfacebound microgels behave similarly as dispersed microgels with respect to their performance as carriers for peptide and protein drugs or whether the presence of the surface will change the situation, for example, through mass transfer limitations, interfacial crowding effects, or interactions between the surface and the protein/peptide.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Smart microgels have emerged as promising materials in numerous biomedical applications, such as biosensing, drug delivery, and enzyme encapsulation because of their unique characteristic features. They are soft colloidal particles composed of a gel-like internal structure with a size typically ranging between tens of nanometers and submicrons. Poly­( N -isopropylacrylamide) (PNIPAM) is a most commonly studied thermoresponsive microgel, which exhibits a volume phase transition temperature (VPTT) at around 32 °C owing to its sharp swollen-to-collapsed phase transition. ,,, Microgel can be made pH-responsive by introducing charged functionality or through an interpenetrated polymer network. , Incorporation of charged units leads to a higher swelling degree of the microgels, allowing oppositely charged counterions, polyelectrolytes, proteins, enzymes, etc. to adsorb strongly onto the particles. Because of the responsive nature, the microgels have been used in the controlled release of drugs. ,, The drug release can be triggered by external stimuli through which the microgels undergo structural change …”
Section: Introductionmentioning
confidence: 99%